COMBINING MATHEMATICS, ECONOMICS AND ECOLOGY TO STRENGTHEN CONSERVATION EFFORTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, February 2016 – The combined expertise in mathematics, economics and ecology would optimise the success and achievements in the conservation process of each country’s rich biodiversity.